2018
DOI: 10.1021/acs.est.8b05246
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure Modulation of Graphitic Carbon Nitride by Oxygen Doping for Enhanced Catalytic Degradation of Organic Pollutants through Peroxymonosulfate Activation

Abstract: Oxygen-doped graphitic carbon nitride (O−CN) was fabricated via a facile thermal polymerization method using urea and oxalic acid dihydrate as the graphitic carbon nitride precursor and oxygen source, respectively. Experimental and theoretical results revealed that oxygen doping preferentially occurred on the two-coordinated nitrogen positions, which create the formation of low and high electron density areas resulting in the electronic structure modulation of O−CN. As a result, the resultant O−CN exhibits enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 525 publications
(171 citation statements)
references
References 36 publications
3
168
0
Order By: Relevance
“…A simple but effective strategy is to modulate rGO by heteroatom doping [64]. Carbon doped with N is expected to possess more lattice defects for regulating the electronic structure, such as sp 2 -hybridized carbon skeletons [65,66]. Kang et al reported that N-doping could significantly improve the activity of reduced graphene oxide (N-rGO) for PMS activation using urea as the nitrogen source [67].…”
Section: Go/rgomentioning
confidence: 99%
“…A simple but effective strategy is to modulate rGO by heteroatom doping [64]. Carbon doped with N is expected to possess more lattice defects for regulating the electronic structure, such as sp 2 -hybridized carbon skeletons [65,66]. Kang et al reported that N-doping could significantly improve the activity of reduced graphene oxide (N-rGO) for PMS activation using urea as the nitrogen source [67].…”
Section: Go/rgomentioning
confidence: 99%
“…The C 1s spectra of CN, pCN-N and pCN-N/ZIS-Z in Figure 5a show three main characteristic peaks at 284.8 eV, 286.2 eV and 288.3 eV, which can be attributed to adventitious carbon species(C-C), sp 3 -bonded carbon C-NH x (x = 1, 2) on the edges of heptazine units and sp 2 -bonded carbon in (N-C=N), respectively [50]. It can be found that pCN-N has a new characteristic peak at 288.7 eV compared to CN, which corresponds to C=O [47], which can be attributed to oxygen-doping. At 288.3 eV, the characteristic peak of pCN-N is weaker than that of CN, which is due to the nitrogen defect in pCN-N.…”
Section: Photocatalyst Characterizationmentioning
confidence: 97%
“…As illustrated in Figure 4b, CN has three distinct sections of characteristic absorption bands. The broad peak in the range of 3000-3500 cm −1 are assigned to the N-H stretching vibrations of -NH x groups (-NH 2 or NH) and O-H stretching vibrations of surplus hydroxyl groups or absorbed water molecules [47]. There are some strong bands between 1200 cm −1 and 1700 cm −1 associated with the stretching vibration of C=N and C-N heterocycles.…”
Section: Photocatalyst Characterizationmentioning
confidence: 97%
“…Nonmetal doping is also considered to be an efficient approach to improve electron transfer capability. Electronic structure modulation was achieved in oxygen-doped g-C 3 N 4 for PMS activation, which was fabricated using urea and oxalic acid dihydrate [66]. The authors further investigated carbon and oxygen doped g-C 3 N 4 exhibited better PMS activity due to its dual active sites-electron-poor C atoms and electron-rich O atoms [86].…”
Section: Chemical Aopsmentioning
confidence: 99%
“…On the other hand, introducing extra sources of reactive species such as H 2 O 2 or PMS in photocatalysis can significantly increase degradation efficiency [64,65]. Furthermore, some studies have explored g-C 3 N 4 based composites for organic pollutants removal without light irradiation in the presence of PMS or H 2 O 2 [66][67][68][69].…”
Section: Introductionmentioning
confidence: 99%